Wearable artificial skin layer for the reconstruction of touched geometry by morphological computation. (2nd November 2018) - Takei, Toshinobu; Ando, Mitsuhito; Mochiyama, Hiromi
ABSTRACT: This paper proposes a wearable haptic sensor for the reconstruction of the surface geometry of an object to be touched. The proposed haptic sensor is a thin rubber artificial skin layer that is formed around the user's finger or other body part and contains a small embedded strain gauge for measuring large deformations. The sensor can be easily fabricated by rubber dipping. First, it was demonstrated that the proposed sensor is not only able to statically detect the curvature of the touched surface but can also measure deformations due to rapid light tapping with robustness against motion noise. As an illustrative demonstration of morphological computation in haptics, it was then demonstrated that it is possible to reconstruct the geometry of tiny undulations in the surface of the touched object from the information obtained by the proposed sensor. GRAPHICAL ABSTRACT: